تطور المكننة في القطر العربي السوري للفترة من عام 1970-1999 وعلاقتها بإنتاج القمح - نصور, محمد عبد الجليل (Latakia University Journal -Biological Sciences Series, 2019)
لقد أصبحت الآلة عنصراً أساسياً في الزراعة المتقدمة حتى أصبح من غير الممكن وجود زراعة متطورة بدون آلات حديثة. تتوقف زيادة الإنتاج الزراعي وتخفيض تكاليفه بشكل رئيسي على مكننة الإنتاج والإدارة الصحيحة للآلات المستعملة فالمكننة الزراعية تشكل العمود الفقري في الزراعة المتطورة على الرغم من أهمية قطاع الزراعة ودوره المميز في واقع ومستقبل الاقتصاد العـربي فإن تطوره لم يبلغ المستوى المقبول لأسباب عدة أهمها ضعف درجة المكننة لمعظم الزراعات. لقد بين البحث الاتجاه العام لتطور الآلات الزراعية ذاتية الحركة في سوريا ودرجة المكننة معبراً بنصيب وحدة المساحة /هـ/ من القوة الميكانيكية /حصان/ ونصيب الجرار الواحد من الأراضي المستثمرة من قدرة جرارات فقط (هـ /جرار) وتأثير هذا التغيير في درجة المكننة على إنتاج القمح في سوريا وعلى غلته. وانتهى البحث إلى ذكر جملة من الاستنتاجات وطرح لبعض الحلول بالإضافة إلى إيجاد علاقات خطية التي بوساطتها يمكن معرفة حاجة القطر من هذه الآلات للاستمرار في ذات المستوى من التطور أو زيادته. Machine has become a major element in advanced agriculture, so that it is not possible to have well developed agriculture without modern machines. Increasing agricultural production and reducing its cost is depend on mechanization of production and on a good management of machines in use. Agricultural mechanization is the backbone in developed agricultural and despite the importance of Agricultural sector and its distinguished role in the Arab economy in the present and in the future. The development of Agricultural mechanization has not reached an acceptable level, for several reasons such as the weak mechanization of plantation. This study shows the general way for the development of Agricultural self-mobile machines in Syria, and the degree of mechanization ( Hectare / Horse and Hectare / Tractor) and the impact of this alteration in the degree of mechanization and on the wheat production and yield. Finally some suggestions and solution have been stated beside a linear equation to determine the needed machines to cope with / or to increase the level of development.